Performance study of a novel multi-functional Trombe wall with air purification, photovoltaic, heating and ventilation - Wu, Shuang-Ying; Xu, Li; Xiao, Lan (Energy conversion and management, 2020)
•A novel PC-PV-Trombe wall with space heating, air purification and photovoltaic power generation.•Multi-physical fields coupling model of flow, heat and mass transfer with photocatalytic reaction.•Effects of channel height and width on the performance of PC-PV-Trombe wall.•Performance comparisons among PC-PV-Trombe wall, built-in PV-Trombe wall and PC-Trombe wall. A novel multi-functional passive solar wall, i.e., photocatalytic-photovoltaic-Trombe wall (PC-PV-Trombe wall), which can obtain heat, electricity and fresh air simultaneously was proposed firstly. Then a multi-physical fields (velocity, temperature and concentration fields) coupling model was established to study the performance of PC-PV-Trombe wall. The effects of channel height and width on the thermal, electrical and degradation performance of PC-PV-Trombe wall were analyzed. Finally, the performance of PC-PV-Trombe wall, built-in PV-Trombe wall and PC-Trombe wall were compared under different solar radiation intensities and ambient temperatures. The results show that the ventilation volume, thermal efficiency, heat output, electrical efficiency and the clean air delivery rate of PC-PV-Trombe wall present different trends of increase or decrease with the change of channel height and width. As opposed to the effect on the electrical efficiency, the lower ambient temperature has a negative influence on the ventilation volume, thermal performance and air purification performance, especially for the condition of lower solar radiation intensity. PC-PV-Trombe wall can realize the comprehensive utilization for air purification, photovoltaic, heating and ventilation of solar energy and the total efficiency can reach a maximum of 0.67.